Long‐term outcome and quality of life after continent ileostomy for ulcerative colitis: A systematic review. (18th July 2021) - Deputy, Mohammed; Worley, Guy; Patel, Komal; Fletcher, Jordan; Hart, Ailsa; Block, Mattias; Øresland, Tom; Myrelid, Pär; Faiz, Omar
Abstract: Aim: The continent ileostomy allows evacuation of an ileal reservoir at a time convenient to the patient. It is a surgical option for patients with ulcerative colitis (UC) when a restorative option is not suitable or has not succeeded and the patient does not want a conventional end ileostomy. Continent ileostomy types include the Kock pouch, Barnett continent intestinal reservoir and T‐pouch. All of the published evidence on the long‐term outcome and quality of life after continent ileostomy for UC was systematically reviewed. Methods: A systematic review was performed in line with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. Studies published between 1990 and 2020 were included. A descriptive synthesis was used due to the clinical heterogeneity. Results: The search returned 1655 abstracts and after screening of abstracts and full text review, 19 were included in the final review, involving 1602 patients. Operative mortality is low (0%–3.6%) after all types of continent ileostomy but reoperation rates are high (20.8%–65%) because of valve mechanism failures. Rates of fistulae (0%–25.5%) and stomal stenosis (0%–25%) can be relatively high postoperatively. Quality of life scores improve for most patients undergoing continent ileostomy, especially for patients converted from ileal pouch anal anastomosis. Overall, continent ileostomy retention is high in the long‐term. Discussion: In the long‐term, patients report high satisfaction and a good quality of life with continent ileostomy, despite high reoperation rates and complications. Newer technologies may reinvigorate interest in the continent ileostomy for this population.